The effect of functional strength training according to gradually increasing load in developing some physical abilities and achievement for men’s 100-meter competition runners - Issa, Fahim; Mohaif, Saleh; shihab, ghadah; Jawad Kadhim, Mohameed (Journal of Physical Education, 2024)
Functional strength is one of the most important elements of physical preparation and an important physical characteristic in our daily life in general and sports training in particular, as it is the most influential characteristic in all sporting events, which the athlete must possess in order to reach the highest levels and achieve the best results. The research aimed to prepare functional strength training exercises According to the gradual increase in load in the development of some physical abilities and achievement for men’s 100 meter competition runners , And to identify the effect of functional strength training according to the gradual increase in load in developing some physical abilities and achievement for men’s 100-meter competition runners. , Hence the importance of research is evident: preparing functional strength training exercises according to the gradual increase in load by providing successful solutions in an economical manner in terms of time and effort and knowing their positive impact in bringing about the required development and improving the level of players in a better way. The problem of the research is that the achievement of the players in this event does not rise to acceptable levels, as a result of the weakness of some of their physical abilities. It has become impossible for them to develop except through training according to a coordinated training curriculum, The researchers used the experimental method with pre- and post-testing for the experimental and control groups. The research population was identified as players in the 100-meter competition for men for the open category for ages over 20 years in the 2021 sports season, and they numbered (10 players). The sample was divided into two groups: the experimental group and the control group, with (5 players) for each. Group, the researchers concluded that functional strength training according to the gradual increase in load has a positive effect on developing some physical abilities and achievement for men’s 100-meter runners. , The researchers recommended Interest in functional strength according to the gradual increase in load has a positive impact on developing some physical abilities and achievement for men’s 100 meter competition runners. , Conduct similar studies and research on different age groups.